Influence of Organic Manures (Biofertilizers) on Soil Microbial Population in the Rhizosphere of Mulberry (Morus Indica L.) - Louis Mary, L. Christilda; Sujatha, R.; Chozhaa, A. J.; Navas, P. Mohideen Askar (International Journal of Applied Sciences and Biotechnology, 2015)
The effect of different kinds of organic manures on soil microbial population and mulberry production was assessed. A field experiment wascarried out at Periyar EVR College, Tamil Nadu, India in basic soil to study the influence of organic manures on soil bacterial population andmulberry production. The 4 groups of mulberry plants of MR2 variety were biofertilized with FYM, Azospirillum, Phosphobacteria andVermicompost respectively. The biofertilizers lodged bacteria on the rhizosphere of mulberry plants. When the root microorganism areanalyzed Farm yard manure biofertilized mulberry plant root tips had Gluconacobacter diazotrophicus, Bacillus pumilus, Pseudomonas putida,Bacillus coagulans, Bacillus sonorensis, Azotobacter chrococcum; Azospirillum biofertilized mulberry plants root tips had Bacillus coaculans,Azotobactor chrococcum, Azotobactor vinelandii, Bacillus subtilis and Azospirillum brasilense. Phosphobacteria biofertilized mulberry plantroot tips had Pseudomonas putida, Bacillus stearothermophilus, Brevibacillus borslelansis and Streptomycies thermonitrificans andvermicompost biofertilized mulberry plant root tips had lodged bacterias like Bacillus megaterium, Bacillus subtilis, Gluconacobacterdiazotrophicus, Pseudomonas putida, Azotobacter chrococcum, Azotobacter vinelandi, Bacillus stearothermophilus, Brevibacillus borslelansisand Bacillus sonorensis. Microbiology work reveals luxuriant growth of bacteria in all the biofertizer treated rhizosphere in the order FYM <Azospirillum < Phosphobacteria < Vermicompost. Increased availability of NPK and other micronutrients were noticed in T4 treated plantscompared to other treatments. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12137 Int J Appl Sci Biotechnol, Vol. 3(1): 61-66